2022
DOI: 10.34172/jlms.2022.12
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Photoinduced Photoacoustic Streaming and Diode Laser Irrigation Techniques on Smear Layer Removal, Sealer Penetration and Push-out Bond Strength

Abstract: Introduction: The present study aimed to test the efficiency of photoinduced photoacoustic streaming using 2940 nm Er: YAG laser and 980 nm diode laser agitation on smear layer removal, sealer penetration and push-out bond strength. Methods: Sixty single canaled human permanent teeth were collected for this study. Specimens were grouped into three experimental groups (20 teeth in each group), depending on the activation protocol used for final irrigation: Group I (needle agitation), group II (980nm diode laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…In accordance with the present result, Akcay et al 6 found that Er: YAG laser activation with PIPS technique and PUI had remarkable better dentinal sealer penetration than CI, also a study by Abdel-Gawad et al 31 reported that the Er: YAG laser (PIPS) possessing the ideal sealing ability and sealer penetration when compared to diode laser and CI. Furthermore, when equivalent root canal thirds were compared, the current results correlate with Eldeeb et al 32 who demonstrated greater sealer penetration following PIPS activation with the exception of the apical third, which had root canal preparation of 25/4%.…”
Section: Moura-netto Et Alsupporting
confidence: 91%
“…In accordance with the present result, Akcay et al 6 found that Er: YAG laser activation with PIPS technique and PUI had remarkable better dentinal sealer penetration than CI, also a study by Abdel-Gawad et al 31 reported that the Er: YAG laser (PIPS) possessing the ideal sealing ability and sealer penetration when compared to diode laser and CI. Furthermore, when equivalent root canal thirds were compared, the current results correlate with Eldeeb et al 32 who demonstrated greater sealer penetration following PIPS activation with the exception of the apical third, which had root canal preparation of 25/4%.…”
Section: Moura-netto Et Alsupporting
confidence: 91%
“…When used in low energy mode, there is less thermally altered layer favoring resin infiltration [17,18]. In Endodontics, Laser tips are used to activate irrigating solution which results in formation of bubbles and consequent evaporation of water molecules leading to efficient removal of smear layer leading to increased bond strength of fibre post to root dentin [19,20].…”
Section: Discussionmentioning
confidence: 99%